Violence and vulnerabilities: Afghans in Pakistan - Sanaa Alimia (Forced Migration Review, 2014)
Given that the majority of Afghans who live in Pakistan today are unlikely to return to Afghanistan, more needs to be done to address their vulnerabilities and protect them from harassment and violence.